2023
DOI: 10.1101/2023.03.15.532773
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global disinhibition and corticospinal plasticity for drastic recovery after spinal cord injury

Abstract: The induction of large-scale plasticity in the adult brain should be key for recovery from severe damage of the central nervous system. Here, drastic motor recovery was observed after subhemisection spinal cord injury in macaques that received intensive training and cortical electrical stimulation. During recovery, movement-related activity increased in ipsilesional sensorimotor areas and functional connectivity from ipsilesional to contralesional areas was strengthened. Electrical stimulation applied widely a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…For example, when the brain or the spinal cord is injured, the brain often recruits normally-underused cortical sensorimotor areas (dorsal premotor cortex [PMd], primary motor cortex [M1], primary somatosensory cortex [S1], and superior parietal cortex of Area 2) during ipsilateral hand/finger movements (Grefkes & Fink, 2020; Hoy et al, 2004; Jang et al, 2004; Lotze et al, 2006; Ward et al, 2008). Recently, animal studies have suggested that such recruitment of ipsilateral sensorimotor cortices is mediated by disinhibition of interhemispheric inhibition between the left and right motor cortices (Yamaguchi et al, 2023) by acetylcholine modulating GABAergic interneurons (Handa et al, 2024). In stroke patients, jamming transcranial magnetic stimulation (TMS) to the ipsilateral sensorimotor cortices disrupts finger movement, especially the TMS to the PMd disrupts the movement more than when it is applied to the M1 and the superior parietal lobule (Lotze et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For example, when the brain or the spinal cord is injured, the brain often recruits normally-underused cortical sensorimotor areas (dorsal premotor cortex [PMd], primary motor cortex [M1], primary somatosensory cortex [S1], and superior parietal cortex of Area 2) during ipsilateral hand/finger movements (Grefkes & Fink, 2020; Hoy et al, 2004; Jang et al, 2004; Lotze et al, 2006; Ward et al, 2008). Recently, animal studies have suggested that such recruitment of ipsilateral sensorimotor cortices is mediated by disinhibition of interhemispheric inhibition between the left and right motor cortices (Yamaguchi et al, 2023) by acetylcholine modulating GABAergic interneurons (Handa et al, 2024). In stroke patients, jamming transcranial magnetic stimulation (TMS) to the ipsilateral sensorimotor cortices disrupts finger movement, especially the TMS to the PMd disrupts the movement more than when it is applied to the M1 and the superior parietal lobule (Lotze et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, this bilateral mode is the first step toward restoring motor function (Grefkes and Fink, 2020). Recent animal studies have suggested that this bilaterally active mode is caused by disinhibition of interhemispheric inhibition between the left and right motor cortices (Yamaguchi et al, 2023) by acetylcholine modulating GABAergic interneurons (Handa et al, 2024).…”
Section: Introductionmentioning
confidence: 99%